MAXILLOFACIAL MANIFESTATIONS OF TUBERCULOSIS: PATHOGENETIC BASIS AND PRINCIPLES OF DENTAL MANAGEMENT - Ibragimov Bakhovuddin Bakhtiyorovich; Khabibova Nazira Nasrullaevna (Web of Journals Publishing, 2025)
Tuberculosis remains a major global health problem with a wide spectrum of clinical manifestations extending beyond pulmonary involvement. Extrapulmonary forms of tuberculosis often affect the maxillofacial region, where lesions may involve the oral mucosa, jaw bones, salivary glands, and facial soft tissues. These manifestations are frequently characterized by atypical clinical presentation, prolonged course, and resistance to conventional dental treatment, which leads to diagnostic delays and inadequate management. The present article analyzes the pathogenetic mechanisms underlying maxillofacial involvement in tuberculosis and substantiates the principles of pathogenetically based dental management. Particular attention is paid to clinical variability, diagnostic challenges, interdisciplinary collaboration, and prevention of complications. The integration of dental care into the overall tuberculosis management system is emphasized as a key factor in improving clinical outcomes and patient safety.
Keywords: Tuberculosis, maxillofacial region, oral manifestations, dental management, pathogenesis.